Pengaruh Pressure, Opportunity dan Rationalization terhadap Financial Statement Fraud pada Perusahaan property dan Real Estate - Radot Christian; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to examine the effect of pressure, opportunity and rationalization on financial statement fraud. The population used in this study are property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The number of research samples obtained was 35 companies using purposive sampling method, then the amount of data in this study was 175. This research method was analyzed by multiple linear analysis and the research tool used was E-views 10. The results of the partial test showed that pressure had a significant effect on financial statement fraud, while opportunity and rationalization have no significant effect on financial statement fraud.